The Impact of Corporate Social Responsibility Disclosure on Financial Performance of Firms in Africa - Mansaray, Amidu P.; Yuanyuan, Liu; Brima, Sesay (International Journal of Economics and Financial Issues, 2017)
In recent years, firms have been pressured by community stake holders to engage in Corporate Social Responsibility (CSR). Many firms have responded to these pressures by implementing CSR activities in their operations, while others have opposed. Firms that opposed to CSR have appealed for a compromise between CSR and profitability. Consequently, this study evaluates the impact of CSR disclosure on the financial performance of firms in Africa for both short and long terms. 158 listed companies were selected from six African countries (South Africa, Kenya, Nigeria, Morocco, Egypt & Mauritius) and grouped into six industry. We measured CSR in terms of keywords count (content analysis) referred to this as CSRdisc. We employed accounting based to measure financial performance of firms (ROA for short-term, and ROE for long-term). Multiple linear regression analysis was done with a sample of panel data for a period of 11 years (2005-2015). Our empirical results showed that unlike for the sales & manufacturing, health & pharmacy and others industries, CSR disclosure affects the financial performance of firms in the short-run (ROA) negatively for the mining, investment and transport industries. We propose that this negative impact is an extra cost burden to the firms. Thus, CSR does not generate economic benefits for the firms in the short-run in those industries. With respect to long-term (ROE) financial performance, majority of our results suggest positive but no significant economic benefits for the firms. Although there is positive relationship between CSRdisc and financial performance of some firms in the long-run, the financial performance of firms in Africa does not depend significantly on their corporate social responsibility practices but rather on other factors, such as their previous performance, leverage, volume of capital, and size. Nevertheless, given the numerous benefits of corporate social responsibility, it is recommended that firms continue to give priority to this practice. Keywords: CSR disclosure, financial performance, firms, ROA, ROE, Africa JEL Classifications: G3, M1